Quantifying the influence of Indian optics research: An index based on three citation indicators - Kappi, Mallikarjun; Biradar , Balabhim Sankrappa (Iberoamerican Journal of Science Measurement and Communication, 2023)
Objective: This study aimed to identify and analyse the characteristics of highly cited papers (HCPs) in optics publications from India indexed in the Web of Science Core Collection database over the past 30 years. The analysis focused on document types, annual production and citations per publication, journals, countries, institutes, authors, and the top cited papers. The study also evaluated the publication performance of institutions and compared citation indicators of the most frequently cited articles. Design/Methodology/Approach: The study used a bibliometric analysis approach and identified HCPs as documents cited 100 or more times by the Web of Science Core Collection from 1992 to 2021. Data were visualised using VOSviewer and Bibliometrix R packages. Citation indicators, including total citations and citations in 2021, were used to compare the most frequently cited articles. Results/Discussion: The results showed that most highly cited papers were published in journals with high impact factors. The USA was the dominant country in collaboration with India in optics publications. The papers by Agostinelli et al. (2003) were the most frequently cited, and the paper by Aghanim et al. (2020) was the most impactful in 2021. The study also found that the Indian Institute of Technology, Delhi, was the leading institution in the number of highly cited papers produced. Conclusions: This study provides insight into the characteristics and trends of highly cited papers in optics publications from India. The results highlight the importance of collaboration with the USA and the significance of publishing in high-impact factor journals. The study also indicates the need for institutions to focus on producing quality research to increase their publication performance and impact. Originality/Value: This study contributes to the literature on bibliometric analysis by comprehensively analysing highly cited papers in optics publications from India. The study also provides insights into the collaboration patterns and publication performance of institutions in India. The findings can be used to inform policies and strategies aimed at improving research productivity and impact in India.